2018
DOI: 10.1007/s10753-018-0785-8
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 and the Bcl-2 Family Proteins Mcl-1, tBid, and Bim Are Involved in Inhibition of Apoptosis During Persistent Chlamydia psittaci Infection

Abstract: Chlamydia psittaci is an obligate intracellular pathogen that can cause zoonosis. Persistent C. psittaci infection can inhibit apoptosis in host cells, thus extending their survival and enabling them to complete their growth cycle. In this study, the antiapoptotic effects of persistent C. psittaci infection, induced by treatment with IFN-γ, were found to be associated with both the death receptor and the mitochondrial pathways of apoptosis. These effects were mediated by Bcl-2 family members, as evidenced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Furthermore, p27 is a CDK inhibitor that has a negative regulatory effect on proliferation and is a downstream target of FOXO1; consequently, FOXO1 inhibits cell proliferation by upregulating p27 (39)(40)(41)(42). The Bim protein belongs to the Bcl-2 protein family and exerts a pro-apoptotic effect on cells (43,44); previous studies have confirmed that FOXO1 regulates cell apoptosis through its downstream targets, including Bim (45,46). The present study confirmed that propofol may regulate miR-374a/FOXO1 signaling to promote the expression of p27 and Bim, and to inhibit the proliferation and promote the apoptosis of ovarian cancer cells, thereby enhancing the sensitivity of ovarian cancer cells to ddP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, p27 is a CDK inhibitor that has a negative regulatory effect on proliferation and is a downstream target of FOXO1; consequently, FOXO1 inhibits cell proliferation by upregulating p27 (39)(40)(41)(42). The Bim protein belongs to the Bcl-2 protein family and exerts a pro-apoptotic effect on cells (43,44); previous studies have confirmed that FOXO1 regulates cell apoptosis through its downstream targets, including Bim (45,46). The present study confirmed that propofol may regulate miR-374a/FOXO1 signaling to promote the expression of p27 and Bim, and to inhibit the proliferation and promote the apoptosis of ovarian cancer cells, thereby enhancing the sensitivity of ovarian cancer cells to ddP.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of host cell apoptosis is a persistent C. trachomatis infection mechanisms [ 42 ]. Current studies have confirmed that persistent C. trachomatis infection affects some apoptotic signaling pathways [ 43–45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that some Inc proteins can inhibit host cell apoptosis, which is essential for Chlamydia infection (Li et al, 2018). C. trachomatis IncG interacts with the mammalian 14-3-3b protein in HeLa cells, and 14-3-3b in turn recruits Bad (a pro-apoptotic protein) to the chlamydial inclusion complex, resulting in inhibition of host cell apoptosis (Scidmore and Hackstadt, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in MMP is a characteristic of the early stages of mitochondrial-dependent apoptosis, in which the up-regulation of the Bax/Bcl-2 ratio causes Cyt.c release into the cytoplasm, and then Caspase-9 and Caspase-3 are activated, accompanied by the lysis of PARP, which eventually leads to cell apoptosis (Bi et al, 2018;Ye et al, 2019). Chlamydia can maintain MMP stability, which might be inseparable from the mechanisms of persistent infection and resistance to host cell apoptosis (Li et al, 2018). CPSIT_0846 can prevent CCCP-induced mitochondrial membrane potential reduction and inhibit the release of Cyt.c into the cytoplasm, which indicates that CPSIT_0846 may inhibit host cell apoptosis by acting on mitochondrial-mediated signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation